2010
DOI: 10.1007/s10765-010-0892-8
|View full text |Cite
|
Sign up to set email alerts
|

Melting Temperature of High-Temperature Fixed Points for Thermocouple Calibrations

Abstract: Thermocouples can be calibrated at pure metal ingot-based fixed points at temperatures up to the freezing point of copper (1084.62 • C). For Pt/Pd thermocouples, the deviation from the accepted reference function very often takes an approximately linear form up to the copper fixed point. The calibration of Pt/Pd thermocouples may therefore be more amenable to extrapolation than that of Pt/Pt-Rh thermocouples. Here, the melting temperatures of a Co-C and a Pd-C eutectic fixed point are determined by extrapolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Their back-gated graphene field-effect transistors have a mobility higher than 4000 cm 2 V -1 s -1 [2]. Wu et al [3] used a solenoid coil to inductively heat copper foils up to 1100 • C-1150 • C beyond the melting point of copper at 1084.62 • C [8]. The reported cooling rate of 60 • C s −1 induced recrystallized copper from the Cu liquid phase and transformation of the Cu domains to Cu(111).…”
Section: Introductionmentioning
confidence: 99%
“…Their back-gated graphene field-effect transistors have a mobility higher than 4000 cm 2 V -1 s -1 [2]. Wu et al [3] used a solenoid coil to inductively heat copper foils up to 1100 • C-1150 • C beyond the melting point of copper at 1084.62 • C [8]. The reported cooling rate of 60 • C s −1 induced recrystallized copper from the Cu liquid phase and transformation of the Cu domains to Cu(111).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature history was recorded at a frequency of 1 kHz by a multiplex temperature recorder connected to K‐type thermocouples, while the feedstock material was deposited. The thermocouples were calibrated with the fixed point method [ 32 ] using the phase changes of water. The time constants of the used thermocouples, defined as the time required to respond to 63.2% of an instantaneous temperature change, were measured for 0.014 s in boiling water, considering that full temperature detection is reached after nearly 0.04 s.…”
Section: Experimental and Methodsmentioning
confidence: 99%
“…This is comprised of a broad spectrum of organisations from industries, research institutes and universities with a common interest in high temperature measurement. These organisations are kept regularly informed through updates on the project website 6 . The website is interactive and enquiries about high temperature measurement problems can be posted.…”
Section: Knowledge Transfer Activitiesmentioning
confidence: 99%
“…
In my previous article [1] I discussed some of the innovations that are taking place at the National Physical Laboratory (NPL) 1 in improving high temperature measurement. Starting with the current defined temperature scale ITS-90 [2, 3], I introduced the concepts of high-temperature fixed points [4], new types of thermocouple for use to 1500°C [5,6] and developments in self-validation for contact thermometry sensors [7] and showed that high temperature measurement is undergoing a quiet revolution throughout the measurement chain. Here I want to set the work at NPL in a broader context of developments in the European Union (EU), again led from NPL, through the European Metrology Research Programme 2 project "HiTeMS: High Temperature Measurement Solutions for Industry".
…”
mentioning
confidence: 99%